KARAKTERISTIK MIKROSKOPIS DAN KOMPONEN BIOAKTIF TANAMAN GENJER (Limnocharis flava) DARI SITU GEDE BOGOR - AGOES M. JACOEB; ASADATUN ABDULLAH; RACHMAWATI RUSYDI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
Yellow velvetleaf (Limnocharis flava) is aquatic plant and known as vegetable and source of bioactive compound but it has aerenchyma system which affects to its proximate. The research purpose was to determine microscopic characteristics of yellow velvetleaf tissues such as leaf, stem, and root tissue. The proximate and bioactive compound from fresh and steam materials were also evaluated. The methods of the research consisted of plant dimension measurement, making of tissue slide by paraffin method in Johansen-TBA series, phytochemical analysis, proximate and carotenoid total analysis. The results showed that leaf tissue was composed by epidermis unilayer containing stoma, a palisades parenchyma layer, spongy parenchyma layer with some aerenchyma system, and vascular bundle. Stem tissue consisted of epidermis unilayer, cortex containing chlorophyll, starch, and some aerenchyma system, and vascular bundle was amphicribral type. Root tissue was composed by rhizodermis, cortex with aerenchyma system, endodermis multilayer, and vascular bundle. Fresh yellow velvetleaf contained 91,76% of moisture, 12,40% of ash, 7,95% of fat, 22,96% of protein, 11,93% of crude fibre, and 219,01 g/g of carotenoid total in its leaf. Its stem contained 95,33% of moisture, 16,38% of ash, 5,62% of fat, 13,23% of protein, 16,12% of crude fibre, and 92,99 g/g of carotenoid total. Steaming decreased crude fibre content, but increased ash, fat, and protein content. Steaming also increased leaf carotenoid total, but decreased stem carotenoid total. Leaf extract contained flavonoid, phenol, reducing sugar, and amino acid. Stem extract was composed by flavonoid, reducing sugar, amino acid. Flavonoid and reducing sugar were major bioactive compounds in this plant.